GENERATIF (MPG) PADA MATA KULIAH TRIGONOMETRI DI FKIP UNIVERSITAS PGRI PALEMBANG - Jayanti, Jayanti; Lusiana, Lusiana (Jurnal Dosen Universitas PGRI Palembang)
AbstracThis research aims to produce a Hypothetical Learning Trajectory in the subject of trigonometry using Generative Learning Model (GLM). Instructional design used consisted of three stages: preliminary design, design of experiment (pilot experiment and teaching experiment), andretrospective analysis. In this study, a series of learning activities are designed and developed in accordance with MPG. Subject were 35 students of second semester of the University of PGRI Palembang. This research resulted in Learning Trajectory (LT), which contains a series of learning process in three activities, namely Determining and using the comparison value right triangle trigonometry, trigonometric angle trigonometry special and comparisons in various quadrants. Results of the research is a study that shows a series of trails Student activity initially linking capabilities with new information that it receives. Furthermore, the strategies used by the student gradually developed in accordance with the Generative Learning Model (GLM) is the preparationstage, focusing stage, the stage of the challenge and the application stage.Keywords: Trigonometry, MPG and Design research